Applying the Routine Activities Theory to Cybercrime: A ‘Cyber’ Capable guardian. - Mabunda, Sagwadi (Journal of Anti-Corruption Law, 2024)
This paper presents the third constitutive element of the Routine Activities Theory, the capable guardian, as a possible response to combatting cybercrime. It suggests a re-imagining of the concept of the capable guardian from its original form to what this study calls the cyber capable guardian. It argues that in order to combat cybercrime successfully, it is necessary to introduce artificial intelligence Technology in the form of machine learning to create a cyber capable guardian which will perform functions that a human capable guardian would not be able to perform. Finally, it discusses section 52 of the Cybercrimes Act, which provides for the Designated Point of Contact (DPoC). It argues that the DPoC would be a suitable capable guardian if it were to be created as an independent agency which is incorporated as a private company in terms of The Companies Act 71 of 2008. It further argues that the DPoC should be established with the chief mandate of combating cybercrime through the creation and operation of the Cyber Capable guardian.